The impacts of non-farming income on rural household energy choices: Empirical evidence from China - Peng, Gang; Zhang, Jie; Tang, Menghang; Duan, Zhimin (Frontiers in Psychology, 2022)
This study uses data from the China Family Panel Studies to analyze the possible impact of non-farming income on household energy choices. We use ordinary least squares and instrumental variable estimation methods to investigate the causal effect of non-farming income on household energy choices. We find that an increase in non-farming income assisted farmers in reducing their use of solid fuels in favor of clean energy. Our heterogeneity analysis, based on the average rural household income and geographical location of the village, shows that the energy upgrade effect of non-farming income is more obvious in high-income areas and suburbs closer to the county seat center. Further, we find that non-farming income has an impact on rural household energy choice mainly through the optimization of household energy-saving appliances and the enhancement of environmental awareness.